2019
DOI: 10.5194/acp-19-13489-2019
|View full text |Cite
|
Sign up to set email alerts
|

What controls the formation of nocturnal low-level stratus clouds over southern West Africa during the monsoon season?

Abstract: Abstract. Nocturnal low-level stratus clouds (LLCs) are frequently observed in the atmospheric boundary layer (ABL) over southern West Africa (SWA) during the summer monsoon season. Considering the effect these clouds have on the surface energy and radiation budgets as well as on the diurnal cycle of the ABL, they are undoubtedly important for the regional climate. However, an adequate representation of LLCs in the state-of-the-art weather and climate models is still a challenge, which is largely due to the la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Schrage and Fink (2012) and Schuster et al (2013) suggested a dominant role played by the NLLJ on the LLSC formation over southern West Africa, because it intensifies the cold air advection and generates shear-driven turbulent mixing. The NLLJ typically forms over land at the end of the day when daytime buoyancy-driven turbulence ceases and the Coriolis force predominates, accelerating the wind towards low pressure (Blackadar, 1957). Although the NLLJ is observed almost every night in West Africa during the monsoon season (Parker et al, 2005;Lothon et al, 2008), this formation mechanism may not be applicable at these low latitudes where the Coriolis force is weak.…”
Section: Introductionmentioning
confidence: 99%
“…Schrage and Fink (2012) and Schuster et al (2013) suggested a dominant role played by the NLLJ on the LLSC formation over southern West Africa, because it intensifies the cold air advection and generates shear-driven turbulent mixing. The NLLJ typically forms over land at the end of the day when daytime buoyancy-driven turbulence ceases and the Coriolis force predominates, accelerating the wind towards low pressure (Blackadar, 1957). Although the NLLJ is observed almost every night in West Africa during the monsoon season (Parker et al, 2005;Lothon et al, 2008), this formation mechanism may not be applicable at these low latitudes where the Coriolis force is weak.…”
Section: Introductionmentioning
confidence: 99%
“…The Sc-Cu transition in other climatological regions was the subject of several studies, most of which were performed over the ocean (e.g., Bretherton et al, 1999;Duynkerke et al, 2004;Sandu and Stevens, 2011;de Roode et al, 2016;Mohrmann et al, 2019;Sarkar et al, 2019) and a few over land (e.g., Price, 1999;Ghonima et al, 2016). In these studies, the stratocumulus is initially coupled with the surface, with convective turbulence produced by the cloud-top radiative cooling.…”
Section: Reviewmentioning
confidence: 99%
“…The main process behind this cooling is the horizontal advection of cooler air from Guinea coast, due to the combination of a maritime inflow (MI) (Adler et al, 2017;Deetz et al, 2018) and the NLLJ (Schrage and Fink, 2012;Dione et al, 2019). The onset time and the strength of the NLLJ, as well as the level of background humidity in the ABL, are crucial for the LLSC formation (Babić et al, 2019b). Indeed, from two cases study, Babić et al (2019b) showed that weaker and later NLLJ onset leads to a reduced cooling, so that the saturation within the ABL may not be reached.…”
Section: Sate Of Artmentioning
confidence: 99%
“…The onset time and the strength of the NLLJ, as well as the level of background humidity in the ABL, are crucial for the LLSC formation (Babić et al, 2019b). Indeed, from two cases study, Babić et al (2019b) showed that weaker and later NLLJ onset leads to a reduced cooling, so that the saturation within the ABL may not be reached. The formation of the LLSC marks the end of the jet phase and the beginning of the stratus phase.…”
Section: Sate Of Artmentioning
confidence: 99%